Mananoligossacarídeo, beta-glucano e antibiótico na alimentação de leitões desmamados - Luna, Uanderson Veríssimo de (2013)
A experiment was conducted with the objective of this study was to evaluate the effect of supplementation with mannan oligosaccharides, ß-glucan and antibiotic in diets for castrated male piglets during the nursery phase (21 to 54 days of age) on performance, morpho-histological characteristics of the intestinal mucosa and occurrence of diarrhea. A total of 368 piglets of the same strain, with average weight of 6.9 kg were distributed in a completely randomized design with four treatments (control - basal diet, without supplementation; 2 - basal diet + 1,500 g mannan oligosaccharides/t of diet; 3 - basal diet + 500 g ß-glucan/t of diet; and 4 - basal diet + 250 g colistin/t of diet) and four replications with 23 animals per experimental unit. Performance was assessed through weight gain, feed intake and feed conversion. The morpho-histological characteristics of the intestinal mucosa studied were villus height, intestinal crypt depth, villus circumference and villus height:crypt depth of duodenum, jejunum and ileum ratio. The occurrence of diarrhea was observed daily by the evaluation of fecal score. Supplementation of mannan oligosaccharides, ß-glucan and antibiotic in the diet of castrated male piglets in the nursery phase did not affect performance and occurrence of diarrhea. Greater villus height and crypt depth in the duodenum and ileum were verified in the animals supplemented with ß-glucan. In the jejunum, greater villus circumference was observed in the animals supplemented with ß-glucan and in the animals that did not receive supplemented diet.